2015
DOI: 10.14238/pi55.4.2015.189-93
|View full text |Cite
|
Sign up to set email alerts
|

Skin prick test reactivity in atopic children and their number of siblings

Abstract: Background Some studies have shown that low birth order is a risk factor for developing atopy, although these results remain inconclusive. Those studies put forth the hygiene hypothesis, which states that early childhood infections in siblings may protect against atopy. Hence, an inverse relationship between family numbers and atopy was found. Atopy may be diagnosed from a history of atopy in an individual or his family, and can be confirmed by specific IgE for allergens or positive skin prick tests.Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…), ash tree (0.9%), fungi (0.9%), latex (0.7%) [12] . A cross sectional study by Beatrix Siregar et al, on 192 subjects found skin prick test positive for pet ownership (52.6%), history excessive breast feeding (32.3%) and cigarette smoke exposure (37.5%) [13] . A study by P Cullinan et al, included 552 children and followed from birth to 5.5 years of age found positive skin prick test for dust mites (9.6%), cat fur (8.5%), grass pollens (8.9%) and other allergens (16.7%) [14] .…”
Section: Discussionmentioning
confidence: 99%
“…), ash tree (0.9%), fungi (0.9%), latex (0.7%) [12] . A cross sectional study by Beatrix Siregar et al, on 192 subjects found skin prick test positive for pet ownership (52.6%), history excessive breast feeding (32.3%) and cigarette smoke exposure (37.5%) [13] . A study by P Cullinan et al, included 552 children and followed from birth to 5.5 years of age found positive skin prick test for dust mites (9.6%), cat fur (8.5%), grass pollens (8.9%) and other allergens (16.7%) [14] .…”
Section: Discussionmentioning
confidence: 99%